Hadiths On The Purpose Of Marriage (Teoantropoecosenteric Analysis) - Neila Hifzhi Siregar; Muhammad Shulhi Alhadi Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Wathi is a need between husband and wife as a safeguard to be safe from immorality such as adultery, masturbation. Husband and wife are two human figures, the purpose of their marriage is to educate children according to Islam, to instill commendable morals such as husband's permission to leave the house, sunnah fasting, etiquette to receive guests, raise children, away from despicable morals, marry off daughters if there are men. the man who proposes to her, who is good and pious, practices hablum minalloh and hablum minannas based on the argument. So that it becomes an example of where they are.